International Research Journal of Ayurveda and Yoga (Aug) - Shrimal, Mukesh; Mishra, Indu; Sharma, Ravi (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda the “science of life” or longevity is the holistic science. Human body is fundamentally composed of Dosha, Dhatu &Mala.Apart from the concept of Dosha, Dhatu, Mala there are so many other concept like Strotas, Koshthanga, Ashya, AngaPratyanaga etc. sthough all the organs have their own importance yet Yakrit (Liver) being the largest organ, has the point of consideration both anatomically and functionally. Liver disease has become a serious and challenging health issue for the medical system of India. The present study deals with the review of Yakrita in terms of liver, Yakritdalyudara in terms of Hepatomegaly, probable causes and their inter relationship, Samprati formation of Yakritdalyudara. Present study deals with the efficacy of “RohitakyadhaChurna” on classical symptoms of Yakritdalyudara and on the commonly practised laboratory findings related with liver diseases.30Patients were randomly selected and divided into two groups, one treatment group and another control group. Duration of medication completed 30 days.